MIKROENKAPSULASI OLEORESIN DAUN SIRIH (Piper betle L) UNTUK PRODUKSI BANDENG (Chanos-chanos forsk) TINGGI LISIN PADA PROSES PENGASAPAN CAIR - Margaretha Tuti Susanti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2008)
On this research have observed liquid smoke’s ability to pursue microbe activity, antimicrobe and antioxidant compounds in betel oleoresin, give preservation effect by pursue microorganism’s growth on Chanos-chanos forsk. Fish Submerge process by liquid smoke with betel oleoresin submerge on presmoking, give optimum result in preserve time eihgt weeks lysine value 26,56 mgr/100gr, with TVB value 7,66 mgr N/100 gr and microorganisme total 9,5 x 10 2 CFU/gr, reach on submerge by betel oleoresin 9% concentration, during 15 minutes, and submerge with liquid smoke 4% concentration during 10 minutes. Result above have contribution with sensoric examine of rather hard texture and very liked flavor